The Effect of Intensive Oxidation of Hydrogen Sulfide from Flue Gases of a Soda Recovery Boiler in the Production of Pulp - Sergey V. Aniskin; Victor S. Kurov (Лесной журнал)
Despite the transition to the Swedish technology for regenerating black liquor from pulp production plants, even in those regions of Russia where the standard daily average levels of hydrogen sulfide and methyl mercaptan in the air of populated areas have been achieved, a number of problems remain with emissions of reduced sulfur. In many cities, onetime concentrations of reduced sulfur, especially at night, may exceed the permissible ones. In addition to flue gas emissions from soda recovery boilers, there are other, less intensive sources of harmful emissions in the cooking, evaporation and wood-chemical workshops, in the causticization and lime regeneration workshops, there are emissions from unorganized sources and from the open surface of wastewater treatment facilities. The population living near such plants feels the unpleasant odor of methyl mercaptan. This study has aimed to develop a new technology for reducing gas emissions of reduced sulfur into the environment, applicaple for different sources. The results of testing an industrial installation for purification of gas emissions from a soda recovery boiler in a scrubber with nozzle irrigation have been presented. Based on the measurements of the technological parameters of the operation mode of the gas purification plant and the determination of the composition of the irrigation solution, the analysis of the results obtained has been performed. During the tests, a high degree of hydrogen sulfide capture at a low pH value has been achieved. It has been established that hydrogen sulfide has been captured as a result of its oxidation before entering the irrigation solution in fine droplets of condensate formed on micron-sized particles of sulfate and sodium carbonate. The results of this study have been compared with the results of the studies conducted by Stanford University and the P.P. Shirshov Institute of Oceanology of the Russian Academy of Sciences. The possibility of hydrogen peroxide formation under our test conditions in the surface layer of fine droplets formed during the condensation of water vapour on dust particles has been analyzed. The suposed cause of the obtained effect has been determined to be the thermomechanical deformation of the surface layer of the droplets.